Exploring the Oxidative Metabolism of Uric Acid and Its Implications in Endothelial Dysfunction - Pinto, Bianca Dempsey (2024)
Uric acid is the end-product of purine metabolism in humans, being present in plasma as urate at concentrations of 50 to 420 µM, with elevated levels indicating hyperuricemia. Initially considered a plasma antioxidant, studies indicate that uric acid can cause oxidative damage, inflammation, and endothelial dysfunction. Our group showed that during inflammation, the peroxidase MPO present in neutrophils oxidizes uric acid, generating reactive species. In this work, in HUVEC cells, another peroxidase capable of reacting with uric acid, peroxidasin (PXDN), was identified. Using mass spectrometry, we identified one of the reaction products of PXDN with uric acid, 5-hydroxyisourate, which decreased when PXDN was inhibited. We also found that uric acid seems to divert the enzyme from its main function, collagen IV crosslinking. Functional assays showed that cell adhesion and migration were decreased in the presence of urate, or when PXDN was inhibited or silenced. Considering these findings, we used proteomic tools to deepen the study of the effects of uric acid on HUVEC. The results showed that uric acid caused changes in the expression of various proteins, such as chaperones, redox signaling proteins, protein degradation, and proteins related to the inflammatory process. As validation of the data obtained, we monitored changes in oxidation levels in HUVEC in the presence of uric acid using the roGFP2-Grx1 probe. Uric acid increased probe oxidation in a concentration-dependent manner, but when PXDN was inhibited, cell oxidation in the presence of uric acid decreased. Additionally, we also showed an increase in uratylated proteins in the presence of uric acid. Finally, using the fluorescent probe Proteostat, we observed an increase in levels of misfolded proteins and protein aggregates in cells treated with uric acid. Lastly, we found that uric acid induces an increase in monocyte adhesion (THP-1) to HUVEC cells, as well as an increase in the expression of adhesion proteins related to the inflammatory process, ICAM and VCAM. Subsequently, we expanded the studies to a protein identified exclusively in uric acid treatments, TRC40.Until then, the only known function of TRC40 was to target proteins to the endoplasmic reticulum. Our studies demonstrate a second function for TRC40, which, when oxidized, assumes another conformation, and possesses chaperone activity, preventing protein aggregation. Using HeLa cells, we showed that TRC40 accumulates in specific regions of the cell and seems to interact with chaperones Hsp70 and Hsp110. Silencing of TRC40 caused a decrease in cell proliferation and viability. Using the roGFP2-Grx1 probe again, we monitored cell oxidation after H2O2 addition, and with the use of the Proteostat probe, we also monitored protein aggregate levels after H2O2 addition. In both cases, control cells recovered much faster from stress, while knockout cells remained with higher levels of oxidation and aggregates for longer periods, suggesting a crucial role of TRC40 for cells to deal with stress caused by the presence of oxidants.